De Sandino aos Contras: Formas e práticas da guerra na Nicarágua - Bataillon, Gilles (2018)
From 1978 to 1987 the political life in Nicaragua was marked by the predominance of armed conflicts. Far from being atypical moments in last century's Nicaraguan history, the two wars often seem like a sequence or a remake of actions that were first attested in the beginning of the century, during the conflicts between liberals and conservatives, specially in the course of Augusto César Sandino's uprising against general Emiliano Chamorro, from 1927 to 1934. The analysis of the Central American wars in the second half of the 20th century presents, for a long time, the opposition of the guerrilla groups praxis against the ones of the regular armed forces. This was originated from the refusal of the dominant groups in allowing subordinate groups to have higher positions.The other guerrilla aimed,in a strict sense, for the conservation of the established order. Theywould become perfectly antagonisticfrom then on. The study of the Nicaraguan civil wars requires different approaches. From the beginning of the 20th century, besides the constitutional references of a liberal democratic model, the references of order and violence are in the heart of the Nicaraguan political experience.